GEODEMOGRAPHY AND DEMOGRAPHY - Hulkaroy, Rajabova (Journal of Geography, Regional Planning and Development, 2025)
Objective: Demography is a multidisciplinary science that examines population dynamics, including birth, death, and migration processes, within socio-historical and economic contexts. The fields of geodemography and demogeography emerged to integrate demographic analysis with geographical factors, enabling deeper insights into population distribution, settlement development, and territorial differences. Although demography’s theoretical foundations are well established, distinctions between geodemography and demogeography remain conceptually blurred, and their practical applications in regional demographic studies require further clarification. This article aims to analyze the similarities and differences between geodemography, demogeography, and regional demography by examining their objects, subjects, methodologies, and roles in understanding population processes. Method: The analysis shows that while demography broadly studies population regeneration and dynamics, geodemography focuses on demographic processes in relation to geographical conditions, and demogeography emphasizes territorial aspects of demographic events. Result: Regional demography, in turn, examines demographic processes within specific administrative or territorial units, addressing practical issues such as employment, settlement planning, and infrastructure development. Novelty: The study clarifies the conceptual boundaries and methodological approaches of geodemography, demogeography, and regional demography, highlighting their interconnections and distinct analytical contributions to the demographic sciences. Understanding these differences is critical for developing effective demographic policies, regional planning strategies, and socio-economic development programs, as well as for training specialists capable of integrating demographic and geographical perspectives in research and practice.